2018
DOI: 10.1111/jeb.13268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spatial connectivity on host resistance in a highly fragmented natural pathosystem

Abstract: Both theory and experimental evolution studies predict migration to influence the outcome of antagonistic coevolution between hosts and their parasites, with higher migration rates leading to increased diversity and evolutionary potential. Migration rates are expected to vary in spatially structured natural pathosystems, yet how spatial structure generates variation in coevolutionary trajectories across populations occupying the same landscape has not been tested. Here, we studied the effect of spatial connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 63 publications
(87 reference statements)
3
14
0
Order By: Relevance
“…We found that plant genotypes interacting with “home” biota showed reduced productivity compared with genotypes within the same community that were exposed to “away” biota. This finding agrees with studies on local adaptation in host–pathogen systems where pathogens tend to be ahead of their hosts in the evolutionary arms race and hence cause more damage to local plants (Höckerstedt et al, ; Kraemer & Boynton, ). As a result, plants can experience below‐ground enemy release and become invasive when introduced to a new continent or as a result of climate‐driven range expansion (Blumenthal, Mitchell, Pyšek, & Jarošík, ; Engelkes et al, ; van Grunsven, van der Putten, Bezemer, Berendse, & Veenendaal, ; Mitchell & Power, ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that plant genotypes interacting with “home” biota showed reduced productivity compared with genotypes within the same community that were exposed to “away” biota. This finding agrees with studies on local adaptation in host–pathogen systems where pathogens tend to be ahead of their hosts in the evolutionary arms race and hence cause more damage to local plants (Höckerstedt et al, ; Kraemer & Boynton, ). As a result, plants can experience below‐ground enemy release and become invasive when introduced to a new continent or as a result of climate‐driven range expansion (Blumenthal, Mitchell, Pyšek, & Jarošík, ; Engelkes et al, ; van Grunsven, van der Putten, Bezemer, Berendse, & Veenendaal, ; Mitchell & Power, ).…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have documented local adaptation within plant species in response to abiotic properties, such as climate and soil properties (Bischoff et al, ; Brady, Kruckeberg, & Bradshaw, ; Macel et al, ) as well as to co‐occurring plant species, their diversity and chemical signatures (Abakumova, Zobel, Lepik, & Semchenko, ; Grøndahl & Ehlers, ; Thorpe, Aschehoug, Atwater, & Callaway, ). Plants also exhibit local co‐adaptation with microbial species, including mycorrhizal and pathogenic fungi (Höckerstedt, Siren, & Laine, ; Johnson, Wilson, Bowker, Wilson, & Miller, ). While the adaptation of individual species to local environments is well documented, knowledge of how this influences community‐level processes is still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pattern we observed suggests that the well‐connected populations are more resistant to pathogen attack, as predicted by spatial co‐evolutionary theory where higher rates of gene flow are predicted to provide the upper hand in the arms race between hosts and their pathogens (Gandon & Michalakis, 2002; Gandon & Nuismer, 2009). Indeed, previous studies in this same network of P. lanceolata populations confirmed disease resistance against the specialist fungal pathogen P. plantaginis to increase with increasing population connectivity (Jousimo et al ., 2014; Höckerstedt et al ., 2018). To date, nothing is known about resistance against viruses in P. lanceolata populations in the Åland Islands.…”
Section: Discussionmentioning
confidence: 99%
“…The net result is that, once these "better adapted clones" emerge, they can be maintained even in the absence of antibiotic exposure. Better exploitation of the host's resources generally implies facilitated transmission between hosts, particularly in highly fragmented pathosystems with low connectivity (1068).…”
Section: The Trajectories Of Microbial Communitiesmentioning
confidence: 99%